THE STRENGTH AND STIFFNESS MODULUS OF THIN LAYER HOT MIX ASPHALT CONCRETE AT VARIOUS TEMPERATURE - Elshawesh, Abdulhakim Mustafa; Setyawan, Ary; Asâad, Sholihin (Jurnal Teknik Sipil, 2014)
AbstractStiffness modulus of asphalt concrete mixture is one of the most important parameters for the flexible pavement design that is very susceptible from temperature and time loading. The stiffness modulus here may be defined as a measure of the load spreading ability of material. The stiffness of asphalt mixture can be measured through various laboratory researches and empirical methods. Various laboratory researches have been employed to measure this property of asphalt such as indirect tensile modulus test, ITSM.The aims of this research were to achieve the viability of using asphalt 60/70 pen with different temperature on strength and stiffness modulus on thin layer HMA (4 cm) compared to Asphalt Concrete Wearing Course (6.8 cm). The other purpose is to get to know the effect of the using thin layer HMA (4 cm) in different climate region. All of the asphalt concrete mixtures of thin layer HMA and AC-WC which were used in this research based on Marshall Mix design according to Indonesian standard (Bina Marga 2010). The laboratories tests which have been conducted in this research were: indirect tensile strength (ITS), unconfined compressive strength (UCS) and indirect tensile stiffness modulus (ITSM) at temperature 10°C, 20°C, 40°C and 60°C.In comparison with the results of indirect tensile strength test, indirect tensile stiffness modulus test and unconfined compressive strength test, it is noticed that the strength and stiffness modulus of thin layer hot mix asphalt was affected by the temperature which the temperature degree might increase to decrease or the way around. From the results of ITSM test for HMA and AC-WC showed that starting from the temperature 20°C to 60°C there is no significant value of stiffness behavior at them. However, there is slight different value at temperature 10°C mixture respectively. Keywords: Thin layer, AC-WC ,